Grid Anchor Lane Detection Based on Attribute Correlation - Qiaohui Feng; Cheng Chi; Fei Chen; Jianhao Shen; Gang Xu; Huajie Wen (Applied Sciences)
The detection of road features is a necessary approach to achieve autonomous driving. And lane lines are important two-dimensional features on roads, which are crucial for achieving autonomous driving. Currently, research on lane detection mainly focuses on the positioning detection of local features without considering the association of long-distance lane line features. A grid anchor lane detection model based on attribute correlation is proposed to address this issue. Firstly, a grid anchor lane line expression method containing attribute information is proposed, and the association relationship between adjacent features is established at the data layer. Secondly, a convolutional reordering upsampling method has been proposed, and the model integrates the global feature information generated by multi-layer perceptron (MLP), achieving the fusion of long-distance lane line features. The upsampling and MLP enhance the dual perception ability of the feature pyramid network in detail features and global features. Finally, the attribute correlation loss function was designed to construct feature associations between different grid anchors, enhancing the interdependence of anchor recognition results. The experimental results show that the proposed model achieved first-place F1 scores of 93.05 and 73.27 in the normal and curved scenes on the CULane dataset, respectively. This model can balance the robustness of lane detection in both normal and curved scenarios.